Triethynylmethanol Derivatives: Stable Acetylenic Building Blocks for Surface Chemistry. Issue 8 (11th January 2017) - Prenzel, Dominik; Sander, Tim; Gebhardt, Julian; Soni, Himadri; Hampel, Frank; Görling, Andreas; Maier, Sabine; Tykwinski, Rik R.
Abstract: The synthesis of non‐conjugated, carbon‐rich building blocks is described, based on a basic scaffold of triethynylmethanol (TEtM). The substitution of the ethynyl groups can be easily varied (including R3 Si, H, Br), and this allows structural tuning for stabilization, synthetic derivatization, and adsorption on Ag(111) or Au(111). X‐ray crystallography helps to explain the surprising stability of the selected derivatives in the solid state, and an unusual form of hydrogen bonding is identified from these analyses. Preliminary efforts to achieve surface‐based reactions on Ag(111) and Au(111) are outlined experimentally and computationally. Abstract : Getting to graphyne : Based on high level DFT calculations, a series of differently modified triethynylmethanol (TEtM) derivatives have been used toward generating 30, 30, 30‐graphyne on either Au(111) or Ag(111). After sublimation of the TEtMs, the metal surfaces were investigated by STM and show interesting two‐dimensional networks, although graphyne remains elusive. X‐ray crystallography of two derivatives shows an unusual form of hydrogen bonding involving the terminal acetylene moieties (see scheme).